(untitled) (Modern education and development, 2025)
Teacher speech is a fundamental communicative tool in educational contexts, shaping not only the transmission of knowledge but also the classroom environment, student engagement, and overall learning outcomes. This article explores the multifaceted role of teacher speech, analyzing its function in instructional delivery, classroom management, student motivation, feedback mechanisms, and relationship building. Drawing on research from educational psychology, linguistics, and pedagogy, the article emphasizes the importance of verbal communication strategies in fostering effective teaching and learning. The study also highlights how adaptive and inclusive speech practices can address diverse student needs and promote equity in the classroom.